Analysis of Imprisonment Implementation against the Perpetrators of the Cybercrimes - Syamsuddin Ishak; Faissal Malik; Suwarti Suwarti (Journal of Social Science, 2023)
This study aims to analyze the application of criminal sanctions to Law Number 11 of 2008 Jo. Law Number 19 of 2016 in the criminal act of defamation or insult decision Number 30/Pid.Sus/2020/PN Tte, and what is the purpose of the threat of imprisonment in the criminal act of mayantara or cyber crime decision Number 30/Pid.Sus/2020/PN Tte about defamation. The research method used in this studyconduct research that is analytical descriptive by using normative legal research or normative juridical. Analytical descriptive legal research is a method that functions to describe or give an overview of the object under study through data or samples that have been collected as they are without conducting analysis and making general conclusions. In other words, analytical descriptive research takes problems or focuses attention on problems as they were when the research was carried out, the results of the research were then processed and analyzed to draw conclusions. The results of this study indicate thatApplication of criminal sanctions by the Panel of Judges for the criminal act of mayantara Decision Number 30/Pid.Sus/2020/PN Tte. regarding Defamation or insult on social media refers to Article 27 paragraph (3) in conjunction with Article 45 paragraph (3) of Law Number 11 of 2008 jo. Law number 19 of 2016 concerning ITE with the threat of imprisonment for 5 (five) years and 6 (six) months and a fine of Rp. 100,000,000.00 (one hundred million rupiah) if the fine cannot be paid by the Defendant, it is replaced by imprisonment for 3 (three) months. However, the Panel of Judges in its Consideration stated that the defendant alias Damrin was legally and convincingly guilty of also committing an act that had a charge that violated decency. The aim of imposing imprisonment on perpetrators of criminal defamation through electronic media is as retaliation for disgraceful acts, as a form of overcoming criminal acts to protect society and to create a deterrent effect on perpetrators. This goal is heavily influenced by criminal philosophies in criminal law.